A new species catfish, Amphilius pagei (Siluriformes: Amphiliidae) from Angola - Thomson, Alfred W.; Swartz, Ernst R. (Zootaxa, 2018)
Amphilius pagei, a new species of amphiliid catfish is described from the Cuanza River basin in Angola. It is distinguished from all other species of Amphilius by the combination of presence (vs. absence) of an epidermal fold at the base of the caudal fin, 6+7 (i,5,6,i) principal caudal-fin rays (vs. 7+8 or 8+9), a variably mottled body coloration that includes dark saddles (vs. body coloration not mottled with dark saddles), head and body heavily spotted (vs. head and body not heavily spotted), epidermal fold smooth (vs. crenelations present on epidermal fold), branchiostegal rays usually eight or nine, and total gill rakers usually 12–16. It is most similar to A. lentiginosus which has a crenelated epidermal fold and fewer branchiostegal rays.